2015
DOI: 10.5812/cardiovascmed.28724v2
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term outcome of pediatric congenital mitral valve surgery

Abstract: Background:Congenital lesions of the mitral valve are relatively rare and are associated with a wide spectrum of cardiac malformations. The surgical management of congenital mitral valve malformations has been a great challenge.Objectives:The aim of this study was to evaluate the early and intermediate-term outcome of congenital mitral valve (MV) surgery in children and to identify the predictors for poor postoperative outcomes and death.Patients and Methods:In this retrospective study, 100 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…To date, only one prospective clinical study of children has been conducted to compare genotype-guided warfarin dose individualisation with the conventional, weight-adjusted dosing approach [12]. Genotype-guided dosing was found to significantly decrease the time to stable dose and hospital stay days [12]. Warfarin dose individualisation in children using PK/PD models has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one prospective clinical study of children has been conducted to compare genotype-guided warfarin dose individualisation with the conventional, weight-adjusted dosing approach [12]. Genotype-guided dosing was found to significantly decrease the time to stable dose and hospital stay days [12]. Warfarin dose individualisation in children using PK/PD models has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that patients with VKORC1 − 1639 AA require significantly lower warfarin doses than the GG or GA groups. Avisa et al [5] reported opposite results, with only two patients with the AA genotype not receiving higher doses. Studies indicated that 1173 and − 1639 SNP are in strong linkage disequilibrium (LD), and even the three SNPs VKORC1 (1173, − 1639, and 3730) might be in LD.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin dosage models based on pharmacogenetics have been generated for adults, but are not used in pediatric patients due to excessive estimation of warfarin dosage. Meanwhile, studies have explored the efficiency of warfarin dose based on genotyping [5, 20, 21], but most of them had small sample sizes and unclear findings. To further define warfarin pharmacogenetics in children, multi-center, randomized control trials are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the study by Baghaei et al, and we congratulate the researchers for the noteworthy objective and results ( 1 ). The author reviewed 100 consecutive pediatric patients with congenital mitral valve disease that underwent mitral valve surgery through median sternotomy.…”
mentioning
confidence: 96%